BRAF Mutated Colorectal Cancer: New Treatment Approaches - Javier Molina‐Cerrillo; María San Román; Javier Pozas; Teresa Alonso‐Gordoa; Miguel Pozas; Elisa Conde; Marta Rosas Cancio-Suárez; Enrique Grande; Laura García‐Bermejo; Alfredo Carrato (2020)
Colon cancer is one of the most frequently diagnosed malignancies in adults, considering both its incidence and prevalence. Anatomically, the right colon is considered as being from the cecum to the splenic flexure, and the left colon is from the splenic flexure to the rectum. Sidedness is a surrogate of a wide spectrum of colorectal cancer (CRC) biology features (embryology, microbiome, methylation, microsatellite instability (MSI), BRAF, aging, KRAS, consensus molecular subtypes (CMS), etc.), which result in prognostic factors. Different molecular subtypes have been identified, according to genomic and transcriptomic criteria. A subgroup harboring a BRAF mutation has been described, and represents approximately 10% of the patients diagnosed with colon cancer. This subgroup has morphological, clinical, and therapeutic characteristics that differ substantially from patients who do not carry this genetic alteration. Unfortunately, there is no established standard of care for this particular cohort of patients. This manuscript aims to study the biology of this subgroup of colon cancer, to understand the current approach in clinical research.